Efektivitas Penyuluhan dalam Meningkatkan Kesadaran Hipertensi di RW 01 Karangbendo - Zada, Al’zena Naura; Safitri, Widya Nur; Febrianti, Reyhan Dwi; Fitriani, Wahidah; Wahyuningsih, Firly; Nadhifa, Naura Rahma; santri, ichtiarini nurullita; Syam, Nur Syarianingsih (Universitas Ahmad Dahlan, 2026)
Hypertension is a chronic medical condition characterized by increased blood pressure in the arteries and is often underestimated by the public. Data show that 32% of residents in RW 01 Karangbendo have been diagnosed with hypertension. This study aims to evaluate the effectiveness of health education in increasing public knowledge about hypertension, including its prevention, impact, and classification. A quantitative method was employed using purposive sampling and a community diagnosis approach. The educational intervention involved 32 respondents and was conducted through lectures and the distribution of educational leaflets. Evaluation was carried out by comparing pretest and posttest results to measure participants' knowledge improvement. The findings indicate that health education significantly enhances public awareness of hypertension. These results highlight that health education through public outreach is an effective strategy for increasing awareness and contributing to hypertension prevention efforts.